Tuberculous gingival enlargement: A rare clinical manifestation - Maria Subash Aaron Muthuraj; Arun Parappa Maradi; Srihari Janakiram; Koshy Chithresan (Wolters Kluwer Medknow Publications, 2017)
Tuberculosis (TB) is an inflammatory granulomatous disease that rarely presents as primary lesion in gingiva. Gingival involvement has been reported in only a very limited number of cases. A 13-year-old boy presented with gingival enlargement in the maxillary and mandibular anterior region associated with enlargement of lower lip with no systemic manifestations. He had a history of tuberculous lymphadenitis before 5 years which was inadequately treated. The patient's erythrocyte sedimentation rate was 70 mm/h. Histopathological report of the gingival lesion revealed noncaseating granulomas with nests of epithelioid cells and multinucleated Langhans giant cells. The patient was then referred to a physician for management, who initiated active antitubercular treatment following which the condition resolved. The aim of this article is to emphasize the importance of early diagnosis of primary TB of the gingiva which may be misdiagnosed when oral lesions are not associated with any apparent systemic infection.